PIPELINE INSPECTION GAUGE (PIG) - MOHD SAFAAI, SHAFIQ SHAHMIN (IRC, 2019)
Pipeline integrity is an important aspect in industry world. Frequent monitoring and assessment on the pipeline transmission line needs to be carried out. Pipeline Inspection Gauge (PIG) has been introduced to perform an In-Line Inspection (ILI) which examine the structural integrity of the pipeline, which uses two inspection tools, namely Magnetic Flux Leakage Tool and Ultrasonic Tool. Data is recorded by PIG and further analyzed by data modelling. Should there be any type of deformities or anomalies detected by the PIG, a corrective and improvement action shall be taken to prevent further failure of pipeline which might injure society and environment. Current prototype has been tested its functionality and its subsystems are working well as it can record the distance travelled, the RGB RAW values, the tilting or orientation angle and all the data has been successfully logged to microSD card. However, further Colour Sensor calibration is crucial to improve the reliability of the prototype as to what it should contribute to the industry. Data analyzation and modelling shall be performed once the prototype has been optimumly calibrated. A laboratory-scaled Arduino-based PIG has been designed and fabricated, hence proving the concept of using RGB colour sensor to inspect the integrity of pipeline system.